The relationship between caries risk assessment using the CAT-AAPD method and the incidence of caries in children - Yusfarani, Mirza Fitria; Dewi, Nurdiana; Wardani, Ika Kusuma (Majalah Kedokteran Gigi Indonesia, 2023)
South Kalimantan Province has a fairly high dental caries problems, and one region with this problem is South Hulu Sungai Regency with a percentage of cases of 45.56%. Dental caries is influenced by various risk factors, including socioeconomic status, eating habits, general health, fluorine use, saliva, and caries experience. Risk assessment of dental caries can be done using the Caries-Risk Assessment Tool by the America Academy of Pediatric Dentistry (CAT-AAPD). This study aims to analyze the relationship between caries risk assessment using the CAT-AAPD method and the incidence of caries in children aged 6-8 years in South Daha District, South Hulu Sungai Regency. This is an observational analytic study with a cross-sectional approach. The population of this study was children in South Daha aged 6-8 years. The total number of samples was 104 selected using the simple random sampling technique. High category caries risk was most common in children suffering from dental caries in a very high category with 64 respondents (53.3%). The results showed that there was a strong relationship (< 0.05) between caries risk assessment using the CAT-AAPD method and the incidence of caries in children aged 6-8 years. The higher the risk of caries, the higher the incidence of dental caries. Parents’ increased awareness of maintaining children’s dental and oral health is important to reduce cases of tooth decay caused by dental caries, and they can determine the treatments that should be undertaken.